The Pheidole ants (Formicidae: Myrmicinae) in the tropical dry forest of Santa Marta, Colombia. (2020)
Ants are a conspicuous biotic component within the tropical dry forest, due to their great diversity both at the species and functional level. Of all the ants, those of the genus Pheidole (Formicidae: Myrmicinae) stand out, which have been categorized as a hyperdiverse group due to the high number of species. The latter has made this group a taxonomic challenge during the development of diversity and ecology studies, therefore, local studies that offer information on the identity of the Pheidole species of a given area becomes an important resource for the decision making. The ants of the genus Pheidole in different formations of tropical dry forest in Santa Marta were studied. Thirteen species are registered, of which Pheidole guajirana extends its distributional range to the department of Magdalena, while P. impressa and P. leptina are registered for the first time in the country. The diagnosis and description of the new species P. urbana is also offered and its morphological features are compared with similar species of the “flavens” informal group. The species richness of the genus in the different sampling sites is evaluated and discussed. Distinctive morphological characteristics are offered for each of the species. Moreover, morphological variability is discussed, and multifocal color images are included for the soldiers (major worker) and workers (= minor worker) of each of the registered species.